Comparison of vasodilator drug prazosin with digoxin in aortic regurgitation. - Hockings, B E (1980)
Intravenous administration of the vasodilator sodium nitroprusside has beneficial haemodynamic effects in subjects with severe aortic regurgitation while acute digitalisation can produce unwanted effects associated with an increase in systemic vascular resistance. This study compares the haemodynamic effects of the vasodilator prazosin and digoxin in eight patients with isolated severe aortic regurgitation. Prazosin 5 mg orally resulted in a 12 +/- 3 (SE) per cent increase in cardiac index (thermodilution), maintained over four to six hours, while digoxin 0.75 mg intravenously did not change the cardiac index. Prazosin reduced mean arterial pressure by 9 +/- 3 mmHg and systemic vascular resistance by 18 +/- 4 per cent while digoxin resulted in a 6 +/- 2 per cent increase in the latter. Mean pulmonary capillary wedge pressure fell 3 mmHg with prazosin. In this group of patients with severe aortic regurgitation but without severe cardiac failure, the changes with either drug, studied in doses conventionally used, were small but those with prazosin were directionally more desirable than those resulting from digoxin.